Fenofibrate enhances lipid deposition via modulating PPARγ, SREBP-1c, and gut microbiota in ob/ob mice fed a high-fat diet - Zhang, Ying; Jia, Xiu-Bin; Liu, Yun-Chao; Yu, Wen-Qian; Si, Yan-Hong; Guo, Shou-Dong (Frontiers in Nutrition, 2022)
Obesity is characterized by triglyceride accumulation in distinct organs. Presently, fenofibrate is a commonly used triglyceride-lowering drug. This study is designed to investigate whether long-term fenofibrate intervention can attenuate lipid accumulation in ob/ob mouse, a typical model of obesity. Our data demonstrated that fenofibrate intervention significantly decreased plasma triglyceride level by 21.0%, increased liver index and hepatic triglyceride content by 31.7% and 52.1%, respectively, and elevated adipose index by 44.6% compared to the vehicle group. As a PPARα agonist, fenofibrate intervention significantly increased the expression of PPARα protein in the liver by 46.3% and enhanced the expression of LDLR protein by 3.7-fold. However, fenofibrate dramatically increased the expression of PPARγ and SREBP-1c proteins by approximately 2.1-fold and 90% in the liver, respectively. Fenofibrate showed no effects on the expression of genes-related to fatty acid β-oxidation. Of note, it significantly increased the gene expression of FAS and SCD-1. Furthermore, fenofibrate modulated the gut microbiota. Collectively, long-term fenofibrate induces lipid accumulation in liver and adipose tissues in ob/ob mice by enhancing the expression of adipogenesis-related proteins and gut microbiota. These data suggest that fenofibrate may have limited effects on attenuating lipid deposition in obese patients.